Normal neurochemistry in the prefrontal and cerebellar brain of adults with attention-deficit hyperactivity disorder - Endres, Dominique; Sobanski, Esther (Frontiers in behavioral neuroscience, 2015)
Attention-deficit-hyperactivity disorder (ADHD) is a common neurodevelopmental disorder. In an attempt to extend earlier neurochemical findings, we organized a magnetic resonance spectroscopy (MRS) study as part of a large, government-funded, prospective, randomized, multicenter clinical trial comparing the effectiveness of specific psychotherapy with counseling and stimulant treatment with placebo treatment (COMPAS study). We report the baseline neurochemical data for the anterior cingulate cortex (ACC) and the cerebellum in a case-control setting. For the trial, 1 480 adult patients were contacted for participation, 518 were assessed for eligibility, 433 were randomized, and 187 were potentially eligible for neuroimaging. The control group included 119 healthy volunteers. Single-voxel proton MRS was performed. In the patient group, 113 ACC and 104 cerebellar spectra fulfilled all quality criteria for inclusion in statistical calculations, as did 82 ACC and 78 cerebellar spectra in the control group. We did not find any significant neurometabolic differences between the ADHD and control group in the ACC (Wilks’ lambda test: p = 0.97) or in the cerebellum (p = 0.62). Thus, we were unable to replicate earlier findings in this methodologically sophisticated study. We discuss our findings in the context of a comprehensive review of other MRS studies on ADHD and a somewhat skeptical neuropsychiatric research perspective. As in other neuropsychiatric disorders, the unclear nosological status of ADHD might be an explanation for false-negative findings.